Assessment of Antimicrobial Potential of Plagiochasma rupestre Coupled with Healing Clay Bentonite and AGNPS. (16th July 2022) - Khan, Muhammad Musa; Bhatti, Qaisar Abbas; Akhlaq, Muhammad; Ishaq, Muhammad; Ali, Daoud; Jalil, Aamir; Asghar, Junaid; Alarifi, Saud; Elaissari, Abdelhamid
Abstract : The impact of individual component, i.e., plant extract ( Plagiochasma rupestre ), biosynthesized silver nanoparticles (AgNPs), and healing clay (bentonite) as antimicrobial agent is reported but their combined effect as a ternary system is a new approach. This study is aimed at investigating the impact of the proposed ternary system against selected human pathogens. AgNPs were synthesized by using Plagiochasma rupestre extract (aqueous) as reducing agent and neutral polymer (PVP) as stabilizer. The morphology, size, and structural properties of synthesized AgNPs were determined with XRD and SEM analysis which showed spherical monomodal particles with an average particle size of 25.5 nm. The antibacterial and antifungal activities of the individual and nanoternary system were investigated. The phytochemical screening of plant extract showed the presence of alkaloids, flavonoids, phenol, and glycosides in methanol extract as compare to aqueous and acetone extract. The antimicrobial activities of crude extracts of Plagiochasma rupestre with AgNPs and bentonite clay were studied as an appropriate candidate for treatment of microbial infections, especially bacterial and fungal diseases. The antioxidant activity of Plagiochasma rupestre aqueous extract and nanoparticles was assessed by (DPPH) free radical, and absorbance was checked at 517 nm. Crude extract has inhibitory effect towards bacteria and fungi, and bentonite clay also showed some degree of antimicrobial resistance. Strategy can be efficiently applied for future engineering and medical. The nanoternary systems showed 3 and 3.5 times higher antibacterial and antifungal activity, respectively, in comparison to Plagiochasma rupestre and bentonite clay, individually.